2020
DOI: 10.1111/poms.13133
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Supply Chain Transparency through Supplier Encroachment

Abstract: This study investigates a supplier’s voluntary disclosure strategy when it can encroach on a retailer’s operations by selling directly to final consumers. The establishment of a direct sales channel expands market potential, induces the supplier to adopt a more frequent disclosure strategy, and ultimately leads to a higher level of information transparency in the supply chain. Since more quality information is revealed in the presence of a dual channel, the retailer is able to free ride on the supplier’s discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 39 publications
(88 reference statements)
1
70
0
Order By: Relevance
“…For example, Tsay and Agrawal (2004) showed that when a supplier takes efforts to promote the product, encroachment could mitigate double marginalization and benefit both parties in the supply chain [21]. Guan et al (2020) demonstrated when the product-quality information is the supplier's private information, encroachment changes his quality-disclosure strategy, and thus, conditionally forms a win-win situation [12]. analyzed the influence of manufacturer encroachment in a supply chain with informative advertising investment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tsay and Agrawal (2004) showed that when a supplier takes efforts to promote the product, encroachment could mitigate double marginalization and benefit both parties in the supply chain [21]. Guan et al (2020) demonstrated when the product-quality information is the supplier's private information, encroachment changes his quality-disclosure strategy, and thus, conditionally forms a win-win situation [12]. analyzed the influence of manufacturer encroachment in a supply chain with informative advertising investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effect of the risk preference  on the retailer's profit Fig. [11][12][13] show that, when the market volatility and the accuracy of the e-commerce platform information are fixed, the manufacturer and e-commerce platform's profits decrease with the manufacturer's increasing risk-aversion coefficient. When the degree of the manufacturer's risk aversion increases to a certain extent, the encroachment strategy will never bring additional profits and the manufacturer will abandon the encroachment strategy.…”
Section: Nuerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recall that the manufacturer discloses information if θ>trueθ˜ and withholds information otherwise. Hence, the consumers' expected quality conditional on nondisclosure is given by trueθ¯=Efalse[θfalse|θ<trueθ˜false]=trueθ˜false/2 (Guo, ; Guo & Zhao, ; Guan & Chen, ; Guan et al, ). In line with Grossman (), we assume that the disclosure is truthful.…”
Section: Model Setupmentioning
confidence: 99%
“…And the parameter θ is sufficient to characterize the quality variation. Note that this assumption is also widely used in operations and marketing literature (see, e.g., Guo, ; Guan & Chen, ; Guan et al, ).…”
mentioning
confidence: 99%